2019
DOI: 10.1111/odi.13209
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of oral squamous cell carcinoma from oral lichen planus by salivary metabolomics

Abstract: ObjectiveThis study was conducted to distinguish salivary metabolites in oral squamous cell carcinoma (OSCC) from those in oral lichen planus (OLP) to identify practical biomarkers for the discrimination of OSCC from OLP.Subjects and MethodsWhole unstimulated saliva samples were collected from patients with OSCC (n = 34) and OLP (n = 26). Hydrophilic metabolites in the saliva samples were comprehensively analysed by capillary electrophoresis mass spectrometry. To evaluate the discrimination ability of a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Metabonomic studies comparing such conditions remain scarce, although multivariate analysis of data from HPLC/MS analysis of saliva has been shown to discriminate oral squamous cell carcinoma from oral lichen planus and oral leukoplakia, although peak identification was not confirmed [50]. A more recent study also found salivary metabolomics could separate lichen planus from oral cancer, finding discriminatory metabolites upregulated in oral cancer included indoleacetate, putrescine and phosphoethanolamine [51]. Oral cancer and precancerous dysplasia have also been separated from other clinically similar lesions including keratosis and inflammation [52].…”
Section: Current Knowledge Of the Salivary Metabolomementioning
confidence: 99%
“…Metabonomic studies comparing such conditions remain scarce, although multivariate analysis of data from HPLC/MS analysis of saliva has been shown to discriminate oral squamous cell carcinoma from oral lichen planus and oral leukoplakia, although peak identification was not confirmed [50]. A more recent study also found salivary metabolomics could separate lichen planus from oral cancer, finding discriminatory metabolites upregulated in oral cancer included indoleacetate, putrescine and phosphoethanolamine [51]. Oral cancer and precancerous dysplasia have also been separated from other clinically similar lesions including keratosis and inflammation [52].…”
Section: Current Knowledge Of the Salivary Metabolomementioning
confidence: 99%
“…Saliva is a biological fluid with features such as ease of sampling, cost-effectiveness, and non-invasiveness that make it a perfect diagnostic specimen, highlighting the importance of developing a method for early detection of OSCC based on validated salivary biomarkers [ 14 , 15 , 16 , 17 , 18 ]. Several well-designed studies recently reported on potential detection methods for oral cancer, suggesting analysis of salivary RNA and proteins [ 19 , 20 ], microRNAs [ 21 , 22 ], metabolites [ 23 , 24 ], glycoprotein [ 25 , 26 , 27 , 28 , 29 ], and the microbiome [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, as yet, no suitable biomarkers are regularly used in clinical practice for the management of oral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, the authors suggested a negative prognostic role of decreased salivary miR-125a levels in association with increased salivary miR-21 levels in OLP patients. Ishikawa et al recently suggested a metabolomics approach to distinguish OLP from OSCC [88]; the authors detected higher levels of 12 salivary metabolites in OSCC patients compared with OLP patients. More specifically, the combination of indole-3-acetate and ethanolamine phosphate showed the best statistical accuracy.…”
Section: Oral Cancermentioning
confidence: 99%